A Phthalocyanine-Based Layered Two-Dimensional Conjugated Metal–Organic Framework as a Highly Efficient Electrocatalyst for the Oxygen Reduction Reaction - Zhong, Haixia; Ly, Khoa Hoang; Wang, Mingchao; Krupskaya, Yulia; Han, Xiaocang; Zhang, Jichao; Zhang, Jian; Kataev, Vladislav; Buechner, Bernd; Weidinger, Inez M.; Kaskel, Stefan; Liu, Pan; et al. (Angewandte Chemie International Edition, 2019)
Layered two-dimensional (2D) conjugated metal–organic frameworks (MOFs) represent a family of rising electrocatalysts for the oxygen reduction reaction (ORR), due to the controllable architectures, excellent electrical conductivity, and highly exposed well-defined molecular active sites. Herein, we report a copper phthalocyanine based 2D conjugated MOF with square-planar cobalt bis(dihydroxy) complexes (Co-O4) as linkages (PcCu-O8-Co) and layer-stacked structures prepared via solvothermal synthesis. PcCu-O8-Co 2D MOF mixed with carbon nanotubes exhibits excellent electrocatalytic ORR activity (E1/2=0.83 V vs. RHE, n=3.93, and jL=5.3 mA cm−2) in alkaline media, which is the record value among the reported intrinsic MOF electrocatalysts. Supported by in situ Raman spectro-electrochemistry and theoretical modeling as well as contrast catalytic tests, we identified the cobalt nodes as ORR active sites. Furthermore, when employed as a cathode electrocatalyst for zinc–air batteries, PcCu-O8-Co delivers a maximum power density of 94 mW cm−2, outperforming the state-of-the-art Pt/C electrocatalysts (78.3 mW cm−2).
CRIS-Team Scopus Importer:2022-04-14
Keywords: catalytic sites; electrocatalysts; metal–organic frameworks; oxygen reduction reaction